Estudo da Qualidade Nutricional de Sementes e da Atividade Antiinflamatória da Lectina do Abelmoschus esculentus (L.) Moench (quiabo) - Soares, Geórgia de Sousa Ferreira (2010)
The human unconventional or alternative feeding consists of foods or parts not normally used, whose nutritional value has been evaluated over the past years. This made the seeds of various plant species to become alternative sources of proteins and lipids for human consumption. The isolation and physicochemical characterization of new molecules of plant foods, with a view to their physiological action in the human body, are used as potential source for the discovery of new bioactive molecules. A particular group of these molecules, the lectins, are proteins of nonimmune origin containing at least one non-catalytic domain of specific binding, and reversible, the carbohydrates. Several lectins have been studied, both in terms of physicochemical and biological characterization. In this context, okra Abelmoschus esculentus (L.) Moench, (Malvaceae), a vegetable widespread in Northeastern Brazil, besides the easy access and low cost, seems to be a promising source in the search for new lectins. However, research on its purification and isolation are still incipient. The objective of this study was to evaluate the nutritional quality of okra seeds, and to detect, purify, and characterize the physicochemical aspects, and to evaluate the herbal and pharmacological potential ( antinocicepitive,cytotoxic anti-inflammatory and antifungal activity) of the isolated lectin present in Abelmoschus esculentus seeds.showed a predominance of total carbohydrates represented by fibers (30.81%) and soluble carbohydrates (6.69%), proteins (22.14%) and lipids (14.01%). The lectin from seed flour was extracted with 0.1 M Tris pH 7.4 with 0.15 M NaCl. The detection of the presence of lectins AES was determined by testing hemagglutination activity and human erythrocytes shows that B (24.00 UH.mP-1), O (21.00 UH.mP-1) and rabbits treated and untreated (74.41 UH. mP-1) were agglutinated by the lectin.The lectin was purified by precipitation with ammonium sulfate and eluted in ion exchange column. Rabbit erythrocytes were selected for testing the inhibition of the hemagglutinating activity (UA) in carbohydrates. Its hemagglutinating activity was inhibited by lactose, fructose and manose. The protein profile of AES analyzed by PAGE-SDS demonstrates that the lectin is purified, presenting two bands of apparent molecular mass between 25 and 14 kDa. The analysis by mass spectrometry showed the monomeric form with 10.29 kDa and its dimer of 20.58 kDa. The biological activity tests of the lectin from AES flour previously purified presented anti-inflammatory and antinociceptive activity and showed no cytotoxicity when compared to erythrocytes from the ABO system. The intravenous pretreatment of animals with AES (0.01, 0.1 and 1 mg / kg) before the administration of the phlogistic agent (carrageenan) significantly reduced the edema by about 15%, 21.6%, 44%. This inhibition is dose dependent with maximum effect at 1mg/kg. The lectin from Albemoschus esculentus shows antinociceptive activity in writhing test induced by acetic acid and the okra seed extracts are able to recognize and inhibit the growth of the dermatophyte Tricophytum rubrum fungus.